Integrated Hygiene Control Strategies in Food Manufacturing: Technologies, Regulations, and Socioeconomic Impacts - Nisansala Chandimali; Jaehoon Bae; Ji Young Hwang; Seon Gyeong Bak; Sun Hee Cheong; Seung Jae Lee (Journal of Food Protection)
In the food manufacturing sector, maintaining industry standards and ensuring consumer health rely fundamentally on the quality and safety of the products. To achieve these objectives, hygiene and environmental control procedures are essential for preserving product integrity and minimizing the risk of contamination. Hygiene practices encompass strict sanitation guidelines, such as regular and thorough hand washing, meticulous equipment sterilization, and stringent requirements for the personal cleanliness of food handlers. Similarly, environmental control measures, such as effective pest management and precise regulation of temperature and air quality, are critical in creating and maintaining optimal conditions for the production of safe food. This article underscores the pivotal role of both hygiene and environmental control in the food manufacturing process for ensuring quality and safety. Drawing from extensive research and industry insights, it explores the best practices and recommended procedures for managing environmental factors and maintaining high hygiene standards. Furthermore, it delves into the impact of technological advancements on the food production landscape, examining how innovations have enhanced the ability to control and improve hygiene and environmental conditions. By addressing these key aspects, the article provides a comprehensive overview of the importance of hygiene and environmental control in modern food manufacturing, highlighting their significance in safeguarding public health and maintaining industry standards.